Issues and Challenges in E-Commerce - Kumar, Raj; Saini, Rakesh Kumar; Singh, Kuldeep (International Journal of Computer Sciences and Engineering, 2018)
E-commerce deals with selling and purchasing of goods and services through internet and computer networks. Ecommerce can enhance economic growth, increase business opportunities, competitiveness, better and profitable access to markets. E-Commerce is emerging as a new way of helping business enterprises to compete in the market and thus contributing to economic success. In this paper, we present and discuss these findings, and identify changes that will be required for broader acceptance and diffusion of e-commerce in India. In this research paper we will discuss about advanced analysis of E-commerce which will comprise of strengths, weaknesses, issues, opportunities and challenges faced by e-commerce in current scenario